Discovery of Novaculina myanmarensis sp. nov. (Bivalvia: Pharidae: Pharellinae) closes the freshwater razor clams range disjunction in Southeast Asia. Issue 1 (December 2018) - Bolotov, Ivan; Vikhrev, Ilya; Lopes-Lima, Manuel; Lunn, Zau; Chan, Nyein; Win, Than; Aksenova, Olga; Gofarov, Mikhail; Kondakov, Alexander; Konopleva, Ekaterina; Tumpeesuwan, Sakboworn
Abstract The razor clam genusNovaculina represents an example of a marine-derived, secondary freshwater group. It was thought to comprise three species:N. gangetica (Ganges and smaller basins in Bangladesh and northwestern Myanmar), N. siamensis (Bang Pakong and Pasak rivers in Thailand and Mekong River in Vietnam), andN. chinensis (lower Yangtze River, China). Here we describeNovaculina myanmarensis sp. nov., an additional species from the Ayeyarwady and Salween basins representing a divergent lineage that appears to be sister toN. gangetica . This new record closes aNovaculina range disjunction between northwestern Myanmar and Thailand. The populations of this novel species share a shallow molecular divergence from each other indicating potential dispersal events between the two distant freshwater basins during the Late Pleistocene. Our ancestral area modeling suggests that the MRCA ofNovaculina crown group was a salt-tolerant freshwater species. The recentNovaculina species most likely originated via allopatric speciation. Our findings highlight that generalist estuarine species could have played the role as a source for bivalve expansions into freshwater and that western Indochina is a separate biogeographic subregion, which is clearly distinct from India. A new synonymy is proposed as follows: Pharellinae Stoliczka, 1870 = Novaculininae Ghosh, 1920 syn. nov.